A mechanical strain-induced 1-aminocyclopropane-1-carboxylic acid synthase gene. - Botella, J R (1995)
Ethylene production is observed in all higher plants, where it is involved in numerous aspects of growth, development, and senescence. 1-Aminocyclopropane-1-carboxylic acid synthase (ACC synthase; S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4.1.14) is the key regulatory enzyme in the ethylene biosynthetic pathway. We are reporting an ACC synthase gene in Vigna radiata (mung bean) that is inducible by mechanical strain. The ACC synthase cDNA AIM-1 was induced by mechanical strain within 10 min, reaching a maximum at 30 min, showing a dramatic reduction after 60 min, and showing no detectable message by 3 hr. The kinetics of induction for AIM-1 was similar to a mechanical strain-induced calmodulin (MBCaM-1) in V. radiata, whereas the kinetics of its decline from maximum was different. When plants were subjected to calcium-deficient conditions, supplemental calcium, calcium chelators, calcium storage releasers, calcium ionophore, or calmodulin antagonists, there was no effect on AIM-1, indicating that the mechanical strain-induced AIM-1 expression is a calcium-independent process. Induction of MBCaM-1 in all cases behaved in the same way as AIM-1, suggesting that they share similar mechanically activated cis- and/or trans-acting elements in their promoter.